Lessons from three oil shocks - Klaus Matthies (Intereconomics, 1993)
Two years ago, in early 1991, the third oil shock since 1973 came to an end. On this occasion, by contrast with the previous crises, the increase in prices that had begun when Iraqi troops occupied Kuwait was only short-lived. Why did oil consumers get off so lightly? Have they drawn the right lessons from the events of the seventies?
Keywords: 330; Energy